Satisfaction of Catholics in Surabaya In Accessing Church Social Media - Yuli Nugraheni; Brigitta Revia Sandy Fista; Merlina Maria Barbara Apul (Jurnal Ilmu Komunikasi dan Bisnis, 2023)
This study focuses on the satisfaction of Catholics in Surabaya in accessing the church's Youtube. The COVID-19 pandemic that has hit the world has also changed how religious people worship. Researchers measure motives and satisfaction with using Youtube. This research was conducted using a quantitative approach with descriptive study and survey research methods conducted online with a sample of 100 Catholics in Surabaya who will be taken using the purposive sampling technique. Respondents are satisfied using the church's Community Social Service Youtube of 2.85. The highest position of respondents lies in the information search indicator; the church's Community Social Service Youtube provides satisfaction in finding information for respondents. While respondents are not satisfied with social interaction indicators, the church's Community Social Service Youtube does not give pleasure when used to fulfil information in establishing social relationships. Academically, the benefits of this research can enrich the study of media communication, mainly social media Youtube. Practically, this research is helpful for the Surabaya Catholic Church Social Commission managers to manage the church's YouTube social media.